Charcoal burning suicides in Hong Kong and urban Taiwan: an illustration of the impact of a novel suicide method on overall regional rates. Issue 3 (26th February 2007) - Liu, Ka Y; Beautrais, Annette; Caine, Eric; Chan, Kathy; Chao, Anne; Conwell, Yeates; Law, Chikin; Lee, Dominic; Li, Pichiang; Yip, Paul
Abstract : Objectives: Following the first case in Hong Kong in 1998, the method of committing suicide by charcoal burning has spread to other communities. This aim of this study was to examine the impact of charcoal burning suicides on both overall suicide rates and older-method suicide rates in Hong Kong and urban Taiwan. Design: Trend analysis of the overall and method-specific suicide rates between 1997 and 2002. Comparison of age and gender profiles of those who committed suicide by charcoal burning and other methods of suicide. Setting: Hong Kong and Urban Taiwan. Main results: Suicides by charcoal burning increased rapidly within five years in both Hong Kong and urban Taiwan. This increase was not paralleled by decreases in suicides by older methods and led to an increase of more than 20% in the overall suicide rates. Those in the 24–39 age range were more likely to choose charcoal burning than other methods. Conclusions: The lack of parallel decreases in the suicides rates of older methods with the rise of charcoal burning suicides suggests limited substitution between the methods. The preponderance of the rise in suicide deaths associated with charcoal burning suggests that its invention, followed by wide media dissemination, may have specifically contributed to the increase in suicides in both regions. As a similar increase was found in urban Taiwan as in Hong Kong, charcoal burning suicide should not be viewed as merely a local health problem and has the potential to become a major public health threat in other countries.